PEMBELAJARAN KEIMANAN BERBASIS TEMATIK DALAM MEMBENTUK KARAKTER IMANI PESERTA DIDIK DI KUTTAB DAARUSSALAAM BANGUNTAPAN BANTUL YOGYAKARTA - Indah Puspa Haji (Kopertais Wilayah III Yogyakarta, 2022)
In modern times there have been phenomena in society due to the failure of education to shape the character of generations. Failure of the role of education in shaping the character of children results in a generation of intellectuals who do not have the character of believers which causes a lack of learning of faith in learning in educational institutions. This research is a type of field research (field research) conducted at Kuttab Daarussalaam, Banguntapan, Bantul, Yogyakarta. Research data collection techniques are observation, interviews and documentation. The results of the study show first, the implementation of thematic-based learning in the Kuttab Daarussalaam Banguntapan Bantul consists of three stages, namely planning which contains syllabus and RKK arrangements; Implementation which includes initial activities, core activities and final activities; Assessment uses two techniques. Tests and contests. Second, forming Imani character in children which is approved by good collaboration between teachers and support. Thematic-based learning in the Kuttab Daarussalaam has contributed to shaping the character of Imani students. It is characterized by the character of students who can be returned with God, fellow human beings, themselves and the environment.